MATINYA DEMOKRASI - Nurhidayat, Nurhidayat (Prodi Ilmu Hukum Universitas Nahdlatul Ulama Indonesia, 2021)
Identity politics does not only exist in Indonesia, even in the United States, identity politics has existed and developed much earlier than in Indonesia. Talking about identity politics, of course, cannot be separated from the interests of groups which are represented as public views. The scheme created by the group changed in such a way that it could not be separated from the goal of mass mobilization. Therefore, the narrative of identity politics is closely attached and becomes the ultimate weapon for groups that have an interest in profiting from it. Politics is an ideal way for people to express their aspirations and demands for change as well as a means of realizing a social order in the life of the state.